Implementing target range oxygen in critical care: A quality improvement pilot study. (February 2021) - Heartshorne, Rosie; Cardell, Jenna; O'Driscoll, Ronan; Fudge, Tim; Dark, Paul
Background: Iatrogenic hyperoxaemia is common on critical care units and has been associated with increased mortality. We commenced a quality improvement pilot study to analyse the views and practice of critical care staff regarding oxygen therapy and to change practice to ensure that all patients have a prescribed target oxygen saturation range. Methods: A baseline measurement of oxygen target range prescribing was undertaken alongside a survey of staff attitudes. We then commenced a programme of change, widely promoting an agreed oxygen target range prescribing policy. The analyses of target range prescribing and staff survey were repeated four to five months later. Results: Thirty-three staff members completed the baseline survey, compared to 29 in the follow-up survey. There was no discernible change in staff attitudes towards oxygen target range prescribing. Fifty-four patients were included in the baseline survey and 124 patients were assessed post implementation of changes. The proportion of patients with an oxygen prescription with a target range improved from 85% to 95% (χ 2  = 5.17, p  = 0.02) and the proportion of patients with an appropriate prescribed target saturation range increased from 85% to 91% (χ 2  = 1.4, p  = 0.24). The improvement in target range prescribing was maintained at 96% 12 months later. Conclusions: The introduction and promotion of a structured protocol for oxygen prescribing were associated with a sustained increase in the proportion of patients with a prescribed oxygen target range on this unit.